Acquired Fanconi syndrome secondary to light chain deposition disease associated with monoclonal gammopathy of renal significance: A case report. Issue 36 (September 2018) - Tu, Haiyan; Mou, Lijun; Zhu, Lina; Jiang, Qifeng; Gao, Dave Schwinn; Hu, Ying
Abstract: Rationale: Renal Fanconi syndrome (FS) is a rare complication of monoclonal gammopathy. It is characterized by the impairment of renal proximal tubular function leading to normoglycemic glycosuria, aminoaciduria, hypophosphatemia, hypouricemia and proximal renal tubular acidosis. Renal impairment in monoclonal gammopathy, without fulfilling the criteria of multiple myeloma, is categorized as monoclonal gammopathy of renal significance (MGRS). Patient concerns: A 54-year-old male presented with progressively aggravated bone pain and limitation of activity was admitted to our department. A proximal renal tubular damage was suggested by hypophosphatemia, compensated metabolic acidosis, renal glycosuria, aminoaciduria, and hypouricemia. M-protein of IgA kappa was detected by immunofixation electrophoresis. Mildly increased plasma cells were found in bone marrow cytomorphologic examination. Renal biopsy revealed diffuse linear monoclonal IgA-kappa light chain deposits along tubular basement membranes (TBMs), while lambda was negative. Electron microscopy showed granular electron-dense deposits along the outer aspect of TBMs. Diagnoses: The patient was diagnosed as FS induced osteomalacia secondary to monoclonal gammopathy of renal significance (MGRS) (IgA-κ type) and LCDD. Interventions: He was treated with bortezomib, supplementation by phosphate, alkali agents, and active vitamin D. He responded well to the treatment symptomatically. Outcomes: We reported a rare case of adult acquired FS with hypophosphatemic osteomalacia secondary to LCDD associated with MGRS and the patient was successfully treated with bortezomib. Lessons: Although few cases of LCDD with isolated symptoms of tubulointerstitial nephropathy, rather than glomerular symptoms have been reported. It still needs to be recognized as a differential diagnosis in monoclonal gammopathy.